Neuronal damage in the interval form of CO poisoning determined by serial diffusion weighted magnetic resonance imaging plus1H-magnetic resonance spectroscopy. Issue 2 (1st August 2001) - Murata, T; Kimura, H; Kado, H; Omori, M; Onizuka, J; Takahashi, T; Itoh, H; Wada, Y
Abstract : In a patient with the interval form of carbon monoxide (CO) poisoning diffusion weighted MRI and proton magnetic resonance spectroscopy ( 1 H-MRS) were serially performed immediately after the appearance of delayed sequelae (the 23rd day after exposure). During the period in which few clear findings were evident on MRI T2 weighted images, a high signal area in the cerebral white matter and relative decrease in the apparent diffusion coefficient (ADCav) were already apparent on diffusion weighted images, with these findings thought to sensitively reflect the tissue injury associated with the onset of sequelae. The decrease in relative ADCav persisted until the 38th day after exposure. Subsequently, ADCav gradually increased, and in the cerebral white matter showed higher values in the 118th day after exposure than immediately after the onset of sequelae. During this period, on 1 H-MRS choline containing compounds showed persistently high values throughout the course, with N-acetylaspartate depletion and the appearance of a lactate peak later in the course. These findings, with regional specificity in the cerebral white matter, reflect the developmental process of the white matter lesions in the interval form of CO poisoning in which demyelination progresses leading to neuronal necrosis. Serial diffusion weighted imaging plus 1 H-MRS measurements are useful in determining the tissue damage and long term outcome of delayed sequelae associated with the interval form of CO poisoning.